2020
DOI: 10.1177/0004865820933332
|View full text |Cite
|
Sign up to set email alerts
|

Community engagement in youth justice program design

Abstract: Aboriginal young people from rural areas in Australia are significantly over-represented in the youth justice system, and yet there is little evidence to indicate that current programs are having measurable success on rates of re-offending, suggesting alternative approaches are required. Drawing on new directions in human service policy that emphasise the importance of involving community in program design, this study reports the findings of a consultation with Aboriginal community members from one rural commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The key qualities of the recommended approach are thus reflected in the use of terms such as “reflexive,” “relational,” “contextual,” “holistic,” “critical,” and “participatory” and share many of the characteristics of mainstream qualitative research methodologies (even though it is important to note that these have not generally been developed using Indigenous epistemologies; Kovach, 2009). In Australia this type of research has, to some extent at least, come to be endorsed in various guidelines (e.g., the CONSIDER statement; Huria et al, 2019) and it is now quite common for non-Indigenous researchers to utilize conversational and narrative methods considered better suited to Indigenous knowledge production (e.g., Butcher et al, 2020) rather than the quantitative or positivist approaches that are employed in most ACEs studies.…”
Section: Indigenous Research Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The key qualities of the recommended approach are thus reflected in the use of terms such as “reflexive,” “relational,” “contextual,” “holistic,” “critical,” and “participatory” and share many of the characteristics of mainstream qualitative research methodologies (even though it is important to note that these have not generally been developed using Indigenous epistemologies; Kovach, 2009). In Australia this type of research has, to some extent at least, come to be endorsed in various guidelines (e.g., the CONSIDER statement; Huria et al, 2019) and it is now quite common for non-Indigenous researchers to utilize conversational and narrative methods considered better suited to Indigenous knowledge production (e.g., Butcher et al, 2020) rather than the quantitative or positivist approaches that are employed in most ACEs studies.…”
Section: Indigenous Research Methodologiesmentioning
confidence: 99%
“…For example, what might be referred to as “culturally-specific” childhood experiences are not recorded in current government databases or ACEs surveys, despite their potential importance. These might include experiences relating to cultural dislocation, losses of cultural practice, forced family removals, and experiences of individual and systemic racism—all of which can be considered potentially traumatic and have been identified as likely to contribute to subsequent youth offending (e.g., Butcher et al, 2020). Child protection authorities have also been criticized for having a disproportionate focus on Aboriginal families and for ignoring cultural differences in child rearing (e.g., Delfabbro et al, 2010), with similar criticisms leveled at the police in relation to the over-surveillance of minority groups.…”
Section: Our Approachmentioning
confidence: 99%
“…This call is based on an expectation that both public administration and non‐Aboriginal organisations will spend time in Aboriginal communities to better understand their unique historical, social, and political contexts when developing both policy and practice. It is through this process of engagement that the community's cultural knowledge, cultural authority, governance structures, and decision‐making protocols can be understood, and genuine partnerships can be formed that contest hegemonic practise, recognise community self‐determination, and Aboriginal heterogeneity (see Butcher et al., 2020; Ramsden, 2002; Williams, 1999). Crucially, it is suggested that through this process of engagement, the perspectives, priorities, and knowledge of Aboriginal communities can be recognised as a legitimate epistemic resource which can then inform the creation of new evidence‐based policies and practices (Australian Government, 2020a; National Indigenous Australians Agency, 2020; Productivity Commission, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence‐based approach to policy and programming has been criticised for ignoring the complex social and political position of Aboriginal people and communities and for not adequately considering Aboriginal ways of knowing, being, and doing (Dudgeon & Kelly, 2014; Pillay, 2017; Tauri, 2017; Williams, 2016). As a result, it has been suggested that some youth justice programmes have limited ecological validity and are not easily transferrable across different communities and contexts (Butcher et al., 2020). Rather, a more pluralistic approach is required that acknowledges the value of more qualitative approaches that engage community values, knowledge, and moralities (Day et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The co-chair of Just Reinvest, Sarah Hopkins, has reflected on the development of a stronger sense of pride and belonging within the community, noting the community are engaging in programmes and activities together, building relationships and feeling a sense of safety within their community (Stanley & Potter, 2020). The community's participation at all levels of the development, delivery, and evaluation stages, alongside using grounded knowledge to build local capacity and feel empowered, has been integral to the results (Allison & Cunneen, 2018;Brown et al, 2012Brown et al, , 2016Butcher, Day, Kidd, Miles & Stanton, 2020;Cunneen et al, 2020;Ferguson & Lovric, 2019;KPMG, 2016KPMG, , 2018Riboldi & Hopkins, 2019;Schwartz, 2010;Stanley & Potter, 2020). In addition, the collective impact approach mentioned earlier has ensured a relatively smooth devolution of power to the Bourke community, enabling cultural authorities to be the decision-makers regarding issues that successive governments have previously failed to mend.…”
Section: Justice Reinvestment In Bourkementioning
confidence: 99%